Bloodfire Quest - Brooks, Terry (New York Ballentine Books, 2013)
A follow-up to "The Wards of Faerie" places the fate of an innocent young girl in the hands of protectors who embark on a dangerous quest to protect a once-peaceful world from dangerous creatures imprisoned behind an eroding magical barrier.
102178
Keywords: Shannara (Imaginary place) -- Elves -- Druids -- Good and evil; Quests (Expeditions); Fantasy fiction, American